2011
DOI: 10.1002/jbm.a.33124
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hydrogen embrittlement of Ni–Ti superelastic alloy in acid fluoride solution by hydrogen peroxide addition

Abstract: Inhibition of the hydrogen embrittlement of Ni-Ti superelastic alloy in an acidulated phosphate fluoride (APF) solution has been attempted by adding various amounts of H(2)O(2). In a 0.2% APF solution, hydrogen absorption is markedly inhibited by adding H(2)O(2), although corrosion is slightly enhanced by increasing the amount of added H(2)O(2). By adding a small amount of H(2)O(2) (0.001 M), in the early stage of immersion, hydrogen embrittlement is inhibited and corrosion is only slightly enhanced. Upon addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…With increasing H 2 O 2 concentration up to 0.01 M in the solution with 0.001 M or 0.01 M NaHCO 3 , the corrosion current density (0.76 ± 0.22 A/m 2 or 0.57 ± 0.17 A/m 2 ) increased near that in the 0.2% APF solution without addition (0.74 ± 0.09 A/m 2 ). As reported previously [26], the increase in H 2 O 2 concentration probably enhances corrosion even in the 0.2% APF solution with NaHCO 3 . The corrosion potential shifted in the noble direction of approximately 0.15-0.2 V with increasing H 2 O 2 concentration.…”
Section: Inhibition Of Corrosionsupporting
confidence: 79%
See 2 more Smart Citations
“…With increasing H 2 O 2 concentration up to 0.01 M in the solution with 0.001 M or 0.01 M NaHCO 3 , the corrosion current density (0.76 ± 0.22 A/m 2 or 0.57 ± 0.17 A/m 2 ) increased near that in the 0.2% APF solution without addition (0.74 ± 0.09 A/m 2 ). As reported previously [26], the increase in H 2 O 2 concentration probably enhances corrosion even in the 0.2% APF solution with NaHCO 3 . The corrosion potential shifted in the noble direction of approximately 0.15-0.2 V with increasing H 2 O 2 concentration.…”
Section: Inhibition Of Corrosionsupporting
confidence: 79%
“…Upon adding H 2 O 2 in the solutions with NaHCO 3 , as shown in Figure 2(b), the corrosion potential shifted in the noble direction with increasing H 2 O 2 concentration (around −0.3 V vs. SCE) and then became stable. The shift is probably associated with the marked growth of the oxide film attributable to H 2 O 2 with high oxidation capability [26,33,34].…”
Section: Inhibition Of Corrosionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be because the post-process etching time was significantly shorter in duration than the original etching treatment. This shorter etching time was used to avoid over etching the retained original CE surfaces, which could lead to hydrogen embrittlement [32]. A slight increase in the oxide peak observed by Raman spectroscopy (see Figure 6) reveals that is was a valid concern, because increasing the crystallinity of Ti can lead to brittleness [33].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In addition, previous studies have reported that electroformed structures contain light elements such as C, O, and N, which are retained in their structure, probably during the manufacturing process 10 . These low-atomic-number elements with small atomic radii can be dissolved in a metallic structure, forming an interstitial solid solution with increased hardness and tensile strength at the expense of ductility and fracture strength, as in the case of hydrogen embrittlement 16 . In addition, they might be implicated in further changes in mechanical properties during porcelain firing, because the firing temperature (780°C) is very close to the melting point of pure Au (1064°C), and various mechanisms might be triggered.…”
Section: Introductionmentioning
confidence: 99%